A simple model for predicting lung cancer occurrence in a lung cancer screening program: The Pittsburgh Predictor. Issue 1 (July 2015) - Wilson, David O.; Weissfeld, Joel
Highlights The Pittsburgh Predictor is a simple 4-factor prediction model for lung cancer occurrence. For 1–5% 6-year lung cancer risk prediction, the Pittsburgh Predictor performs well. The Pittsburgh Predictor may facilitate standardized procedures for advising and selecting patients with respect to lung cancer screening.